2007
DOI: 10.1017/s0022149x07868775
|View full text |Cite
|
Sign up to set email alerts
|

Infection of red foxes with Echinococcus multilocularis in western Switzerland

Abstract: In the Jura mountains, Plateau and Alps of western Switzerland important variations in the prevalence of Echinococcus multilocularis infection in red foxes were observed between geographical areas from 1990 to 1995. The Jura mountains and the Plateau had higher mean prevalence levels than the Alps with 30.6, 32.4 and 18.8%, respectively. The highest rate was recorded in the Plateau in the canton of Fribourg with a prevalence of 52.3%. The prevalence of E. multilocularis infection in foxes in the alpine canton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…in Switzerland (Brossard et al 2007;Reperant et al 2007) or Austria (Duscher et al 2006). In fact, the prevalence rate is similar to the ones obtained from other alpine regions, such as the Swiss canton of Grisons (< 14·3%) (Tanner et al 2006) or the Bolzano and Trento provinces, in northern Italy (< 12·9%) (Manfredi et al 2002;Casulli et al 2005) (Fig.…”
Section: Distribution Of E Multilocularis In Foxessupporting
confidence: 62%
“…in Switzerland (Brossard et al 2007;Reperant et al 2007) or Austria (Duscher et al 2006). In fact, the prevalence rate is similar to the ones obtained from other alpine regions, such as the Swiss canton of Grisons (< 14·3%) (Tanner et al 2006) or the Bolzano and Trento provinces, in northern Italy (< 12·9%) (Manfredi et al 2002;Casulli et al 2005) (Fig.…”
Section: Distribution Of E Multilocularis In Foxessupporting
confidence: 62%
“…The association between parasite burden and age in foxes [11, 26, 27] suggested the use of an age-stratified SIR model originally developed by Roberts et al [30]. It stratifies the host population into compartments that represent their infection and immune status at a particular age and the transition between states can be described by a set of ordinary differential equations.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been carried out on E. multilocularis transmission in foxes in Switzerland providing an extensive prior knowledge for model construction and hypothesis formulation. Previous studies of E. multilocularis in Switzerland have shown that transmission dynamics in animal hosts are influenced by multiple interrelated factors that contribute to its spread [11, 17, 2628]. Decreasing parasite prevalences along with the increasing level of urbanization have been reported in foxes in the two largest cities of Switzerland [11, 27, 28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations